PERANCANGAN SISTEM INFORMASI DATA ALUMNI BERBASIS WEBSITE DENGAN METODE WATERFALL (STUDI KASUS : SDS PERMATA SARI I) - Muhamad Deden Ramdhani; Nur Nafara Rofiq (CV. Multi Kreasi Media, 2022)
With the rapid advancement of technology, educational institutions need an alumni data information system. Having an alumni data website has a very important meaning for schools as a means of information media in obtaining information about alumni data. At primary school educational institutions each year graduate students after undergoing a school period of 6 years. The problem in this study is that the school in inputting alumni data stored in Microsoft Excel on a computer in this administrative room can cause data loss if the computer is damaged, and there are difficulties in finding student alumni data, because the data stored in the computer has too much data every year of graduation. The research method used is the Waterfall using a UML (Unified Modeling Language) diagram to model the website to be created.-based alumni data information system website is expected to be able to overcome the problems that exist in Permata Sari I Private Elementary School.